2015
DOI: 10.1001/jamafacial.2014.782
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Based Decision Analysis of Postreduction Imaging in the Management of Mandibular Fractures

Abstract: IMPORTANCE Immediate postreduction imaging is a standard practice in the management of mandibular fractures at many hospitals. However, the literature suggests that postreduction imaging in maxillofacial fractures fails to influence clinical decision making significantly. OBJECTIVES To determine the cost-effectiveness of different clinical decision pathways regarding postreduction imaging as it relates to the experience of the surgeon, and to demonstrate that baseline postreduction imaging has utility based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Various authors have demonstrated that reflexive postreduction imaging rarely alters clinical management. 2,20,21 Although a single postoperative CT scan is only a minor component of the entire OBF repair, it is an easily identifiable source of radiation exposure and healthcare costs that may be obviated in lieu of careful postoperative clinical examination. Further delineation of reflexive postoperative CT findings after isolated OBF repair is needed to help more clearly define its role, if any, at all.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have demonstrated that reflexive postreduction imaging rarely alters clinical management. 2,20,21 Although a single postoperative CT scan is only a minor component of the entire OBF repair, it is an easily identifiable source of radiation exposure and healthcare costs that may be obviated in lieu of careful postoperative clinical examination. Further delineation of reflexive postoperative CT findings after isolated OBF repair is needed to help more clearly define its role, if any, at all.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its prominence and distinction as the only mobile bone in the face, the mandible is the second most common site of facial fracture after the nose, with assaults and motor vehicle collisions being the leading causes of these injuries (1,2). Twenty-three percent of the 400 000 emergency department visits for facial fractures in the United States in 2007 involved the mandible (3,4). In patients who undergo facial fracture reduction, the mandible is the most frequently reduced bone (5).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, evidence‐based recommendations are needed, as this information can be used to enhance the physician‐patient communications process and guide appropriate test utilization. Decision‐tree based cost‐effectiveness analyses have been performed for a variety of topics relevant to the practicing otolaryngologist . The objective of this study was to perform an economic evaluation focusing on whether routine CT of the neck (from the skull base down to the thoracic inlet or aortic arch) represents a cost‐effective practice in the management of patients with UVFP with no apparent cause.…”
Section: Introductionmentioning
confidence: 99%
“…Decision-tree based cost-effectiveness analyses have been performed for a variety of topics relevant to the practicing otolaryngologist. [5][6][7][8][9][10][11][12] The objective of this study was to perform an economic evaluation focusing on whether routine CT of the neck (from the skull base down to the thoracic inlet or aortic arch) represents a cost-effective practice in the management of patients with UVFP with no apparent cause. Analysis was restricted to vocal fold paralysis and did not evaluate its cost-effectiveness in cases of paresis.…”
Section: Introductionmentioning
confidence: 99%